Faktor Protektif Dan Risiko Perilaku Nonsuicidal Self-Injury Pada Perempuan Dewasa Awal Korban Perselingkuhan Dalam Hubungan Berpacaran - Taqilla, Tanya; Dian Ariana, Atika (CV RIFAINSTITUT, 2023)
Infidelity victims experienced negative emotions such as feelings of hurt, extreme anger, depression, anxiety, and disappointment. They certainly need coping strategies to face their problem but maladaptive coping strategies are often used by victims of infidelity, such as self-harm without a motive for suicide (nonsuicidal self-injury). This study used a qualitative research method with an intrinsic case study approach involving three informants. The data collection process was carried out through interview techniques and by using data driven thematic analysis as a data analysis technique. The results of this study suggest that the protective factors of NSSI behavior in early adult women who are victims of infidelity in dating relationships are realizing that this behavior should not be carried out, having a desire to seek for professional help, wanting to love themselves, and having support from the social environment. Risk factors of this behavior include having done NSSI before, having suicidal intentions, difficult to communicate problem with others, and having another problem along with the experience of being infidelity victim.